Diagnosis of isolated hepatic tuberculosis in an immunocompetent individual: a case report and review of misdiagnosed cases - Li, Lei; Zhang, Jianjun; Song, Qitai; Cheng, Lingxia (Frontiers in Medicine, 2025)
IntroductionHepatic tuberculosis is a rare disease entity even in endemic areas of Mycobacterium tuberculosis. It is usually accompanied by pulmonary tuberculosis or enteric tuberculosis. Due to the non-specific clinical symptoms and imaging features may lead to misdiagnosis and even unnecessary surgery.Case presentationA 44-year-old woman presented with complaints of abdominal pain for the past 2 months. The patient was diagnosed with a solitary hepatic tuberculosis abscess that was identified by abdominal CT and liver biopsy. The patient was started on anti-tuberculous therapy (isoniazid, rifampin, ethambutol, pyrazinamide). One month after diagnosis, an abdominal ultrasound showed the abscess had enlarged to approximately 4.4 cm × 3.4 cm, with heterogeneous echogenicity and internal septations. The patient subsequently went to a specialist hospital for further treatment. Telephone follow-up revealed that the patient continued anti-tuberculosis treatment, with symptoms gradually improving and essentially resolving after 6 months.ConclusionHepatic tuberculosis is relatively rare in clinical practice and can easily be misdiagnosed as hepatocellular and cholangiocellular carcinoma, leading to unnecessary surgery. Postoperative pathological examination confirms the diagnosis of hepatic tuberculosis. A solitary tuberculous liver abscess creates a clinical barrier for treating physicians. We summarized cases that have been misdiagnosed as tumors over the past 20 years. When encountering suspicious patients clinically, it is important to inquire in-depth about the history of tuberculosis and to perform an ultrasound-guided liver lesion biopsy for pathological examination as early as possible to achieve early diagnosis and treatment.